Efficacy of a recombinant turkey herpesvirus (H9) vaccine against H9N2 avian influenza virus in chickens with maternal-derived antibodies - Pan, Xue; Liu, Qinfang; Niu, Shiqi; Huang, Dongming; Yan, Dawei; Teng, Qiaoyang; Li, Xuesong; Beerens, Nancy; Forlenza, Maria; de Jong, Mart C. M.; Li, Zejun (Frontiers in Microbiology, 2023)
Although vaccines have been widely used for many years, they have failed to control H9N2 avian influenza virus (AIV) in the field in China. The high level of maternal-derived antibodies (MDAs) against H9N2 virus contributes to the H9N2 influenza vaccine failure in poultry. The study aimed to generate a new vaccine to overcome MDAs interference in H9N2 vaccination in chickens. We used turkey herpesvirus (HVT) as a vaccine vector to express H9 hemagglutinin (HA) proteins. The recombinant HVT expressing H9 HA proteins (rHVT-H9) was successfully generated and characterized in primary chicken embryonic fibroblasts (CEFs). Western blot and indirect immunofluorescence assay (IFA) showed that the rHVT-H9 consistently expressed HA proteins. In addition, the rHVT-H9 had similar growth kinetics to the parent HVT. Preliminary animal experiments showed that compared to the conventional inactivated whole virus (IWV) vaccine, the rHVT-H9 stimulated robust humoral immunity in chickens with passively transferred antibodies (PTAs) that were used to mimic MDAs. Transmission experiments showed that the rHVT-H9 induced both humoral and cellular immunity in chickens with PTAs. Furthermore, we used mathematical models to quantify the vaccine’s efficacy in preventing the transmission of H9N2 AIV. The results showed that the rHVT-H9 reduced the virus shedding period and decreased the reproduction ratio (R) value in chickens with PTAs after homologous challenge. However, the vaccination in this trial did not yet bring R < 1. In summary, we generated a new rHVT-H9 vaccine, which stimulated strong humoral and cellular immunity, reducing virus shedding and transmission of H9N2 AIV even in the presence of PTAs in chickens.